Semantic and functional peculiarities of proper names in poetry of I.Zhilenko, O.Zabuzhko, Y.Pokalchuk (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Multi-aspect of semantic and functions of main groups of proper names in I.Zhilenko’s, O.Zabuzhko’s, Y.Pokalchuk’s poetry are described. The author proves that proper names are important means of creation of image, economical way of expression of meaning of poetry. They favor information richness of poetry, create its intellectual base.
Keywords: proper name; semantic; poetry